2008
DOI: 10.1073/pnas.0710748105
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of cyclin D1 transcript elongation by a mutated transcription factor up-regulates the oncogenic D1b splice isoform in cancer

Abstract: Pre-mRNA splicing and polyadenylation are tightly connected to transcription, and transcriptional stimuli and elongation dynamics can affect mRNA maturation. However, whether this regulatory mechanism has a physio/pathological impact is not known. In cancer, where splice variant expression is often deregulated, many mutated oncogenes are transcriptional regulators. In particular, the Ewing sarcoma (EwSa) oncogene, resulting from a fusion of the EWS and FLI1 genes, encodes a well characterized transcription fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
110
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(115 citation statements)
references
References 36 publications
5
110
0
Order By: Relevance
“…The relative inability of DOXO to favour inclusion of cassette exons and internal ALEs (Fig. 1c,d) likely stems from its lack of inhibition of transcription elongation 23 , which mediates exon inclusion in response to CPT and UV 19,21,56 . Cassette-exon skipping and internal ALE repression are frequently induced by both DOXO and CPT 22 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The relative inability of DOXO to favour inclusion of cassette exons and internal ALEs (Fig. 1c,d) likely stems from its lack of inhibition of transcription elongation 23 , which mediates exon inclusion in response to CPT and UV 19,21,56 . Cassette-exon skipping and internal ALE repression are frequently induced by both DOXO and CPT 22 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that YK-4-279 blocking of specific protein interactions from EWS-FLI1, such as RHA and p68, will alter the splicing program differently from the loss of EWS-FLI1. We also considered whether EWS-FLI1-modulated RNA pol II elongation activity was affected by YK-4-279 treatment, because this mechanism led to alternative poly(A) site selection for cyclin D1 (17). We did not note any alteration in polymerase elongation activity when stalled complexes were released; however, polymerase effects based on YK-4-279 treatment cannot be fully eliminated based on this limited investigation.…”
Section: Yk-4-279 Alters Splicing Rather Than Direct Transcriptional mentioning
confidence: 99%
“…In addition, previous protein interaction studies identified the SF1 and U1C splicing factors as partners of EWS-FLI1 and discovered that EWS-FLI1 alters the splicing of an adenoviral transcript (14,15). Also, EWS-FLI1 has been shown to modify the IGFBP3 mRNA half-life (16) as well as directly slow the rate of RNA polymerase activity during cyclin D transcription, leading to a more oncogenic isoform, cyclin D1b (17). In total, these studies suggest functionally significant EWS-FLI1 activity in addition to transcriptional regulation driven by DNA binding (16).…”
mentioning
confidence: 99%
“…Finally, it has also been reported that an oncogenic fusion between the multifunctional RBP EWS and the transcription factor FLI1, which is found in Ewing's sarcoma, can influence production of D1b. While EWS itself was shown to promote production of full-length D1a, the EWS-FLI1 fusion promoted production of D1b (Sanchez et al 2008). This was proposed to occur due to impaired transcription elongation in the presence of the fusion protein, which would allow more time for polyadenylation to occur in intron 4 before transcription of E5.…”
Section: Cyclin D1mentioning
confidence: 99%